2017
DOI: 10.1002/biof.1395
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin inhibits NLRP3 inflammasome‐dependent pyroptosis by activating the Nrf2 signaling pathway in vascular endothelial cells

Abstract: Increasing evidence demonstrates that pyroptosis, pro-inflammatory programmed cell death, is linked to atherosclerosis; however, the underlying mechanisms remain to be elucidated. Dihydromyricetin (DHM), a natural flavonoid, was reported to exert anti-oxidative and anti-inflammatory bioactivities. However, the effect of DHM on atherosclerosis-related pyroptosis has not been studied. In the present study, palmitic acid (PA) treatment led to pyroptosis in human umbilical vein endothelial cells (HUVECs), as evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 60 publications
5
89
0
Order By: Relevance
“…The results from other present studies indicate that DHM improves pyroptosis and concomitantly alleviates IL-1β secretion by activating the Nrf2 signaling pathway to inhibit ROS-dependent NLRP3 inflammasome activation in palmitic acid (PA) induced HUVECs [23]. LncRNA revealed in several recent studies can function as a molecular sponge or a competing endogenous RNA (ceRNA) in modulating expression and biological functions of miRNAs [24].…”
Section: Morphological and Molecular Features Of Pyroptosismentioning
confidence: 59%
“…The results from other present studies indicate that DHM improves pyroptosis and concomitantly alleviates IL-1β secretion by activating the Nrf2 signaling pathway to inhibit ROS-dependent NLRP3 inflammasome activation in palmitic acid (PA) induced HUVECs [23]. LncRNA revealed in several recent studies can function as a molecular sponge or a competing endogenous RNA (ceRNA) in modulating expression and biological functions of miRNAs [24].…”
Section: Morphological and Molecular Features Of Pyroptosismentioning
confidence: 59%
“…DHM inhibited PA-induced high-temperature cell death by increasing cell viability and reducing caspase-1 and IL-1β release to improve cell membrane integrity. is study showed that DHM pretreatment significantly reduced intracellular ROS and mtROS levels and activated the Nrf2 signaling pathway [104]. In summary, these results suggested that the Nrf2 signaling pathway was obviously partially involved in the DHM-mediated improvement of PA-induced vascular events, suggesting the potential medicinal value of DHM against immune/inflammation-related diseases such as atherosclerosis.…”
Section: Natural Medicine and The Treatment For Asmentioning
confidence: 64%
“…Beside, studies also showed the regulation effect of Nrf2 on pyroptosis. It was shown activating the Nrf2 signaling pathway could inhibit NLRP3 inflammasome‐dependent pyroptosis in vascular endothelial cells . Li et al also demonstrated erythropoietin could rescue primary rat cortical neurons by regulation of pyroptosis through Erk1/2‐Nrf2/Bach1 signal pathway .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown activating the Nrf2 signaling pathway could inhibit NLRP3 inflammasome-dependent pyroptosis in vascular endothelial cells. 48 Li et al also demonstrated erythropoietin could rescue primary rat cortical neurons by regulation of pyroptosis through Erk1/2-Nrf2/ Bach1 signal pathway. 13 In our study, we for the first time showed At last, we also demonstrated the effects of CPF on miR-181 and revealed the regulation effects of miR-181 on SIRT1/PGC-1α/Nrf2 pathway, cell pyroptosis, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%